Effect of layer integrity of spin self-assembled multilayer films on surface wettability - Cho, Jinhan (Langmuir : the ACS journal of surfaces and colloids, 2004)
We investigated the correlation between surface wettability and internal structure of polyelectrolyte (PE)/PE and PE/inorganic multilayer films prepared by the spin self-assembly (SA) method. Spin self-assembled poly(allylamine hydrochloride) (PAH)/poly(sodium 4-styrenesulfonate) (PSS) multilayer films deposited from PE solutions of 10 mM show the distinct oscillation in contact angles with variation of the outermost PE layer, representing the saturated values in contact angles of individual PAH and PSS layers. These contact angles are also well consistent with the angles measured from respective PE layers (i.e., PAH and PSS) of the spin SA (PAH/CdS-COO-) and (CdS-NH3+/PSS) films carrying the flat interface between PE and inorganic CdS nanoparticle layers as confirmed by X-ray reflectivity. Furthermore, based on the contact angle of CdS-NH3+ layer in the ordered (CdS-NH3+/PSS) films, the change in surface wettability of CdS-NH3+ layers of two different spin SA (CdS-NH3+/poly(methacrylic acid) (PMAA)) multilayer films with ordered and disordered internal structure is also investigated. The films with ordered and disordered internal structure were fabricated by the pH adjustment of PMAA. The CdS-NH3+ layer in both CdS-NH3+/PSS and CdS-NH3+/PMAA multilayer films with the ordered internal structure has the contact angle of about 25 +/- 2 degrees irrespective of the PSS or PMAA sublayer. As a result, the same surface wettability of PE or inorganic layers, despite different sublayers, strongly indicates that the spin SA method in optimum condition allows the top surface to be completely covered with a low level ofinterdigitation with a sublayer at each deposition step, and this leads to the conclusion that physical and chemical characteristics of the sublayers have no significant influence on those of the outermost layer